A review of recent innovative strategies for controlling mycotoxins in foods. (February 2023) - Hamad, Gamal M.; Mehany, Taha; Simal-Gandara, Jesus; Abou-Alella, Sarah; Esua, Okon J.; Abdel-Wahhab, Mosaad A.; Hafez, Elsayed E.
Abstract: Mycotoxin contamination of foods from mycotoxigenic fungi such as Aspergillus, Alternaria, Fusarium and Penicillium spp. is a significant threat to food safety and quality. Aflatoxins, ochratoxins, fumonisins, deoxynivalenol, zearalenone, trichothecenes and patulin have been demonstrated to show immune toxicity, carcinogenicity, nephrotoxicity, hepatotoxicity, neurotoxicity and teratogenicity activities in humans and animals. Implementation of the prerequisite programs like the HACCP-based procedures can reduce mycotoxin contamination, while conventional chemical, biological and physical methods can be employed for detoxification after contamination. But the increasing fungal resistance and challenges associated with the conventional systems necessitate the development of innovative strategies for rapid elimination with short processing time and negligible impact on quality. This review evaluated recent innovative strategies of cold atmospheric plasma (CAP), polyphenols and flavonoids, magnetic materials and nanoparticles and natural essential oils (NEOs) for controlling mycotoxin in foods. Although the available studies indicated the promising potential of these strategies, complete decontamination was not achieved. The mechanisms for the reduced bioactivity of mycotoxins included the disruption of fungal cell membrane and structural degradation of complex biochemical molecules by the oxidative effects of reactive species, inhibition of enzymes responsible for breakdown of carbohydrates and adsorption and binding of functional groups of mycotoxins in food substrate. Integrated management systems of combining multiple strategies can be explored for achieving higher efficiency and better adaptability to different food matrices. Additional studies on the toxicity of the food matrices, degraded products and industrial up-scaling are necessary for ensuring widespread adoption and cost-effective commercialisation for sustainable food processing. Graphical abstract: Image 1